2002
DOI: 10.1101/lm.44302
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampus and Memory of Verbal and Pictorial Material

Abstract: Recognition of words and kaleidoscope pictures showed a double dissociation of left and right hippocampal activity using magnetic source imaging (MSI). MSI has advantages over alternative imaging techniques that measure hemodynamic changes for identifying regional changes in brain activity in real time and on an individual subject basis without the need for image subtraction. In this study, lists of words or kaleidoscope pictures were presented for memorization followed by tests of list items and foils during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 32 publications
8
50
0
2
Order By: Relevance
“…Similar hemispheric specialization of medial-temporal lobe structures in subserving verbal and nonverbal tasks has been demonstrated in functional MRI studies (Kelley et al, 1998;Kirchhoff, Wagner, Maril, & Stern, 2000;Wagner et al, 1998) and PET studies (Haier et al, 1992), both of which showed selective activation of the right hippocampus during visuospatial tasks. Hemispheric specialization has also been suggested in magnetoencephalography studies that show activation of the left hippocampus during word recognition and activation of the right hippocampus during visual recognition tasks (Breier, Simos, Zouridakis, & Papanicolaou, 1999;Papanicolaou et al, 2002). Consistent with this specialization of function across cerebral hemispheres in the mesial temporal lobe, we found that PIQ correlated significantly and more strongly with hippocampus volume in the right than in the left hemisphere.…”
Section: Regional and Hemispheric Specializationsupporting
confidence: 88%
“…Similar hemispheric specialization of medial-temporal lobe structures in subserving verbal and nonverbal tasks has been demonstrated in functional MRI studies (Kelley et al, 1998;Kirchhoff, Wagner, Maril, & Stern, 2000;Wagner et al, 1998) and PET studies (Haier et al, 1992), both of which showed selective activation of the right hippocampus during visuospatial tasks. Hemispheric specialization has also been suggested in magnetoencephalography studies that show activation of the left hippocampus during word recognition and activation of the right hippocampus during visual recognition tasks (Breier, Simos, Zouridakis, & Papanicolaou, 1999;Papanicolaou et al, 2002). Consistent with this specialization of function across cerebral hemispheres in the mesial temporal lobe, we found that PIQ correlated significantly and more strongly with hippocampus volume in the right than in the left hemisphere.…”
Section: Regional and Hemispheric Specializationsupporting
confidence: 88%
“…The results indicated task-related activity in the striatum, but typically not in the hippocampus or other medial temporal lobe structures Seger & Cincotta, 2005;Seger, Peterson, Cincotta, LopezPaniagua, & Anderson, 2010). This pattern of results is consistent with procedural learning, and opposite what one would expect if unstructured-category learning was mediated by explicit memorization (e.g., Papanicolaou et al, 2002;Poldrack et al, 2001). For several reasons, however, these results by themselves cannot be considered diagnostic.…”
supporting
confidence: 73%
“…The two different modalities of the stimuli make correlational fMRI analyses difficult, since memory for pictures and words appears to involve different anatomical regions (Kelley et al 1998;Squire 2000, 2001;Papanicolaou et al 2002). Instead, both phases were presented in pictorial form.…”
Section: Methodsmentioning
confidence: 99%